Evaluating Surgical Resection Extent and Adjuvant Therapy in the Management of Gliosarcoma - Jin, Michael C.; Liu, Elisa K.; Shi, Siyu; Gibbs, Iris C.; Thomas, Reena; Recht, Lawrence; Soltys, Scott G.; Pollom, Erqi L.; Chang, Steven D.; Hayden Gephart, Melanie; Nagpal, Seema; Li, Gordon (Frontiers in Oncology, 2020)
Introduction: Gliosarcomas are clinically aggressive tumors, histologically distinct from glioblastoma. Data regarding the impact of extent of resection and post-operative adjuvant therapy on gliosarcoma outcomes are limited. Methods: Patients with histologically confirmed gliosarcoma diagnosed between 1999 and 2019 were identified. Clinical, molecular, and radiographic data were assembled based on historical records. Comparisons of categorical variables used Pearson's Chi-square and Fisher's exact test while continuous values were compared using the Wilcoxon signed-rank test. Survival comparisons were assessed using Kaplan-Meier statistics and Cox regressions. Results: Seventy-one gliosarcoma patients were identified. Secondary gliosarcoma was not associated with worse survival when compared to recurrent primary gliosarcoma (median survival 9.8 [3.8 to 21.0] months vs. 7.6 [1.0 to 35.7], p = 0.7493). On multivariable analysis, receipt of temozolomide (HR = 0.02, 95% CI 0.001–0.21) and achievement of gross total resection (GTR; HR = 0.13, 95% CI 0.02–0.77) were independently prognostic for improved progression-free survival (PFS) while only receipt of temozolomide was independently associated with extended overall survival (OS) (HR = 0.03, 95% CI 0.001–0.89). In patients receiving surgical resection followed by radiotherapy and concomitant temozolomide, achievement of GTR was significantly associated with improved PFS (median 32.97 [7.1–79.6] months vs. 5.45 [1.8–26.3], p = 0.0092) and OS (median 56.73 months [7.8–104.5] vs. 14.83 [3.8 to 29.1], p = 0.0252). Conclusion: Multimodal therapy is associated with improved survival in gliosarcoma. Even in patients receiving aggressive post-operative multimodal management, total surgical removal of macroscopic disease remains important for optimal outcomes.